Living Waters or Resource? Ontological differences and the governance of waters and rivers. Issue 3 (4th March 2022) - Laborde, Sarah; Jackson, Sue
ABSTRACT: This paper addresses the ontological differences between modern water, the dominant way of thinking about water in the industrialised West, and Living Waters, a concept used by Aboriginal Australians to talk about water(s) and water bodies. Working collaboratively with Aboriginal experts and state government water planners in the Kimberley region of Western Australia we developed two social-ecological conceptual models to compare propositions about the ontological character of water. One model represents a modern water paradigm, upon which state systems of water management are based, and the other represents a customary system of management: a Living Waters paradigm that depicts the relationships between people, other beings, and the waters of the Martuwarra/Fitzroy River catchment. The models are intended to inform water governance processes and influence negotiations between State and customary institutions. We use the models here to analyse water policy tools and their ability to support the relationships particular groups have with their waters. We identify gaps in existing policy for the sustainability of Living Waters. We discuss the implications of the differences between these two conceptual models for water justice, as well as for sustainability research and socio-ecological modelling as it applies to rivers and their waters in Australia and elsewhere, or to other human-environment relationships.